Unveiling the Urobiome: Getting to know Actinotignum schaalii and its role as a potential uropathogen - Ms Jamisha Francis; Ms Mollie Gidney; Mr. Seth Reasoner; Mr. Johnathan Schmidtz; Ms. Maria Hadjifrangiskou (International Journal of Infectious Diseases)
Introduction: The human urobiome, comprising diverse microbial members, plays a crucial role in maintaining urinary tract health. One urobiome member identified in many studies to date – including our group - is Actinotignum schaalii. A. schaalii is a Gram-positive facultative anaerobe that has also been implicated in urinary tract infections in certain patient populations. There is a scarcity of data on the prevalence of Actinotignum in the urobiome given its fastidious growth requirements. This study focuses on the identifying the prevalence of Actinotignum species and identifying conditions necessary for its growth. Methods: In collaboration with Vanderbilt University Medical Center's clinical microbiology laboratory, we collected 350 de-identified random urine specimens. To identify and characterize the presence of Actinotignum in the urobiome we used a combination of Expanded Urine Culture (EUC), 16S rRNA amplicon sequencing, and targeted PCR that allows the propagation and identification of low abundance bacteria. Bacterial identification following EUC was performed using MALDI-TOF and standard laboratory techniques. To characterize features of A. schaalii, we used a reference strain of A. schaalii CCUG 27420 to test growth conditions and performed scanning and transmission electron microscopy. Results: From randomly collected urine samples, we detected Actinotignum species in 20% of specimens by 16S rRNA sequencing. No patient factors readily associated with the presence of Actinotignum. We were able to identify corresponding bacterial colonies by EUC. Growth of the reference strain A. schaalii CCUG 27420 was promoted by the addition of a chemically defined lipid media to BHI (brain heart infusion) broth, specifically arachidonic and myristic acid. We generated high-resolution electron microscopy images of A. schaalii to characterize its cellular morphology. Scanning electron micrographs determined the shape of A. schaalii as a coccobacillus. Transmission electron micrographs detected the presence of an s-layer, metal storage organelles, and intracellular vesicles. Discussion: We detected Actinotignum spp. in urine samples from subjects across a range of ages and medical conditions, suggesting that Actinotignum is prevalent and not limited to specific disease states. Our preliminary data indicates that A. schaalii growth is promoted by lipids. Conclusion: To date, no study has investigated the prevalence of Actinotignum in the community or its growth conditions. This study underscores the importance of leveraging high-throughput sequencing and culturing techniques for a comprehensive understanding of microbial dynamics in the urobiome. The identification of growth conditions for Actinotignum species expands our knowledge of urobiome ecology and sets the stage for mechanistic studies on the interactions of Actinotignum with the urobiome. Ultimately, elucidating the role of Actinotignum in the urobiome may pave the way for targeted therapeutic interventions and personalized approaches to urinary tract health management.